THE INFLUENCE OF TEACHER TEACHING SKILLS AND THE USE OF MEDIA ON LEARNING MOTIVATION AND PHYSICS LEARNING OUTCOMES FOR STUDENTS AT SMAN 2 GOWA - Nursyamsi B; Helmi Abdullah; Kaharuddin Arafah (Universitas Negeri Medan, 2022)
This study is an ex-post facto research with causality. The outbreak of this virus has had an extraordinary impact on various sectors including the education sector, so learning is carried out online with alternative methods utilizing cyberspace, but teachers must provide digital teaching materials to fulfill learning outcomes. The purpose of this study was to describe the description of teachers' teaching skills, media utilization, learning motivation and physics learning outcomes. In addition, this research was also conducted to analyze the direct effect of teacher teaching skills on learning motivation and learning outcomes in physics, to analyze the direct effect of using media on learning motivation and learning outcomes in physics, to analyze the direct effect of using media on learning motivation and learning outcomes in physics. physics learning outcomes and analyze the direct influence of learning motivation on physics learning outcomes. The research sample consisted of 180 students consisting of nine classes. The data collection process was carried out using 3 questionnaires and a physics learning achievement test totaling 21 tests that had been tested empirically. Research data were analyzed using the path analysis method with the Analysis of Moment Structures (AMOS) version 22 technique. The results of the descriptive analysis: teacher teaching skills in the skilled category, media utilization in the very high category, learning motivation in the very high category, and physics learning outcomes in the category tall